Determination of Optimal Parameters of the Ground Filling During the Laying of Power Cable Lines - Vysotski, M. E. (Ėnergetika (Minsk, Belarus), 2025)
The present article discusses the problem of the technical and economic efficiency of using materials with increased thermal conductivity when filling trenches of power cable lines. The specific thermal resistance of the soil significantly affects the permissible cable currents and, as a result, the choice of their cross-section. When the soil dries out or it is initially of high thermal resistance, the carrying capacity of the conductors decreases, which often forces the use of cables with a larger cross-section to provide the required load current. One of the ways to improve cooling conditions is to use a special backfill with lower thermal resistance values, which is more expensive than the ground one. This raises the question of the feasibility of such a solution, since more expensive materials may not pay off in some cases. An optimization technique is proposed based on the calculation of reduced costs, taking into account the cost of cable, line construction and operating costs. The model that has been developed takes into account the influence of both normal and post-emergency operation modes. It is shown that increasing the cable current capacity due to special backfilling can reduce the cable cross-section by one step and, thus, compensate for the cost of more expensive material. Otherwise, the use of special backfills becomes impractical. To solve the optimization problem, a genetic algorithm implemented in the MS Excel environment was used. The results of calculation examples are presented, showing that the proposed methodology and algorithm can be used for various voltage and laying conditions, allowing the designer to select effective parameters of the cable line design.